White Matter Integrity Is Associated With the Amount of Physical Activity in Older Adults With Super-aging - Kim, Bori R.; Kwon, Hunki; Chun, Min Young; Park, Kee Duk; Lim, Soo Mee; Jeong, Jee Hyang; Kim, Geon Ha (Frontiers in Aging Neuroscience, 2020)
Previous studies have introduced the concept of “SuperAgers,” defined as older adults with youthful memory performance associated with increased cortical thickness of the anterior cingulate cortex. Given that age-related structural brain changes are observed earlier in the white matter (WM) than in the cortical areas, we investigated whether WM integrity is different between the SuperAgers (SA) and typical agers (TA) and whether it is associated with superior memory performance as well as a healthy lifestyle. A total of 35 SA and 55 TA were recruited for this study. Further, 3.0-T magnetic resonance imaging, neuropsychological tests, and lifestyle factors related to cognitive function, such as physical activity and duration of sleep, were evaluated in all participants. SA was defined as individuals demonstrating youthful performance of verbal and visual memory, as measured by the Seoul Verbal Learning Test and the Rey-Osterrieth Complex Figure Test, respectively. Tract-based spatial statistics analysis was used to compare the diffusion values such as fractional anisotrophy (FA), mean diffusivity (MD), radial diffusivity (RD) and axial diffusivity (AD) between the SA and TA. SA exhibited better performance in memory, attention, visuospatial, and frontal executive functions than TA did. SA also exhibited greater amounts of physical activity than TA did. As compared to TA, SA demonstrated higher FA with lower MD, RD, and AD in the corpus callosum and higher FA and lower RD in the right superior longitudinal fasciculus, which is significantly associated with memory function. Interestingly, FA values of the body of corpus callosum were correlated with the amount of physical activity. Our findings suggest that WM integrity of the corpus callosum is associated with superior memory function and higher level of physical activities in SA compared to TA.